Sharps injury in Hospital Universiti Kebangsaan Malaysia (HUKM): Experiences of health care workers and students - Santhna L.P,; Samsiah M,; Raja Lexshimi RG,; Ho S.E,; Roshdinom R,; Hamidah H, (Penerbit UKM, 2007)
Sharps injury among health care workers in HUKM has received serious attention lately due to the possible transmission of diseases like HIV, Hepatits B and Hepatitis C, which can cause serious consequences for the victim. The aim of the study was to gain a deeper understanding of the emotional problems experienced by health care workers who had incurred a sharps injury and the coping strategies adopted by them to overcome the problem. A 28 item semi-structured questionnaire was designed by the supervisors and the researcher as there was no existing questionnaire to be adopted, as no research had been carried out in this area prior to this. The target group consisted of 64 health care workers of different categories working in HUKM. Data was collected over a period of five months from November 2000 to March 2001. The results of the study revealed that the most frequently injured were the staff nurses, nearly 90% of whom were emotionally upset and were worried that they might contract a disease. There was no significant difference in the emotional stress experienced by the different categories of the health care workers, all were equally upset about the injury but each category of staff adopted different methods to overcome the tragedy. Open comments and opinions about prevention and the management of the sharps injury in HUKM as given by the respondents here are taken into account. Several views given by the participants were explored and discussed. Finally, several implications for nursing and recommendations have been presented